Late Fines on Paylater Tiktok Services: A Review of Civil Law and a Compilation of Sharia Economic Law - Yuswalina -; Sandy Wijaya; Kurnia Rahmawati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Advances in financial technology have driven the use of “pay-later” services on e-commerce platforms, including TikTok PayLater. However, the regulations regarding late payment penalties in these services raise academic questions due to differences in legal framework between the Civil Code (KUH Perdata) and the Compilation of Sharia Economic Law (KHES). This study aims to analyze the validity of applying late payment penalties on TikTok PayLater from the perspectives of civil law and Islamic economic law, as well as to identify the points of divergence in their regulations. The study employs a literature review (library research) using a normative legal approach. Primary data was obtained from the TikTok PayLater terms of service, while secondary data was sourced from legislation, the KHES, and relevant literature. The data were analyzed qualitatively using documentation techniques. The results indicate that a late payment penalty of IDR 80,000 per 25 days is justifiable under the Civil Code (KUH Perdata) pursuant to Article 1243, provided it is based on a breach of contract and has been validly agreed upon by the parties. Conversely, based on KHES, the legal relationship in such services is more appropriately classified as a qardh contract; thus, the imposition of penalties that provide additional benefits to the creditor has the potential to conflict with the principle prohibiting riba. From a Sharia perspective, penalties for late payment are only justified in the form of ta’widh as compensation for actual losses, not as an instrument that generates profit. Thus, this study confirms the existence of a discrepancy between the regulations on late payment penalties in civil law and Sharia economic law regarding the TikTok PayLater practice.